Producción sostenible de filamento PET con botellas reciclables en la Universidad de América para impresoras 3D (2024)
This project aims to have a significant impact for the Universidad de América Foundation, focused on the management of common waste. The University of America has focused on simplifying the separation of waste, including paper, cardboard and plastic. It has been observed how this approach has transformed the recycling operation and the knowledge of individuals with the reuse of waste, focused in this work on PET bottles discarded in this environment. The project focuses on the manufacture of filament for 3D printers, using recycled PET bottles. This approach is not only geared towards filament production, but also towards reducing PET bottle waste. As recycling grows significantly, there is a positive impact on the environment. The problem focused on citizen awareness in relation to recycling and waste separation is addressed, in the same way that the process is simplified for citizens. This contributes to the protection of the environment and the progress of the implementation of waste recycling, including plastic, paper and cardboard, avoiding the exposure of this waste in the natural environment.